2017
DOI: 10.1007/s10508-017-0968-7
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates of Sexlessness Among American Adults and Associations with Self-Reported Happiness Levels: Evidence from the U.S. General Social Survey

Abstract: Although sexual activity is commonly believed to be a key component of emotional well-being, little is known about the factors associated with the absence of sexual activity or its associations with self-reported happiness. Using the U.S. General Social Survey–National Death Index 2008 dataset, a series of nationally representative surveys (1988–2002), this study analyzed the sociodemographic and life style factors associated with past-year sexlessness and self-reported happiness among American adults (n = 17,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 49 publications
3
26
1
2
Order By: Relevance
“…Our result was similar to those found by Lugoboni et al [18], who found that older age was significantly associated with sexual inactivity. Several studies in other populations reported similar findings [14,20]. Increasing age was also the predictive factor for sexual inactivity in both married and single/divorced subgroups.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our result was similar to those found by Lugoboni et al [18], who found that older age was significantly associated with sexual inactivity. Several studies in other populations reported similar findings [14,20]. Increasing age was also the predictive factor for sexual inactivity in both married and single/divorced subgroups.…”
Section: Discussionsupporting
confidence: 63%
“…The prevalence of sexual inactivity in this study is higher than in other populations. The prevalence of male sexual inactivity in the general population in the US and Britain are 15.2% and 15.9%, respectively [10,20]. The prevalence reported in patients receiving opioid replacement treatment by Lugoboni et al [18] was comparable to the general population, but was four times lower than found in our study.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The prevalence for young men 4,7e9,13,16,23,29,31,32,34,40,43 and middle-aged men 7,9,10,15,27,28,34e38,43 ranged from 1.3% to 83.6% and 1.2%e67.7%, respectively. Furthermore, age categorization in the selected studies showed that the prevalence of secondary sexual abstinence for 10-to 19year-old men ranged from 1.3% to 83.6%, 4,7,9,13,16,29 while for 15-to 24-year-old men, it ranged from 10.2% to 50.3%. 8,13,16,23,31,32,34,40,43 Based on the age categories given in the selected studies, the prevalence of secondary sexual abstinence was 0%e50.3% for men from 18 to 30 years old, 9,15,40,43,44…”
Section: Primary Sexual Abstinencementioning
confidence: 99%
“…The possible factors affecting sexual inactivity are aging, medical (eg, sexual dysfunction, painful intercourse, poor general health, and prevention of sexually transmitted diseases [STDs]), 7e10 lifestyle (eg, not using alcohol, cigarettes, or drugs), 11e14 behavioral (eg, low sexual desire disorder, asexuality, and homosexuality), 11,15 psychological (eg, personal beliefs, low sexual self-esteem, feeling nervous, fear to drop out of school or concentrate on education, guilt and feelings of being used, low sexual satisfaction, painful intercourse, performance anxiety, and depression), 8 relationship with partner (eg, quality of relationship with partner, not comfortable with partner, partner not enjoying sex, and practicing faithfulness), 8,16 family and friends (eg, sexually inactive friends, family encourages abstinence, nonfamilial role model, living alone with single parent or other guardians), 12,14,17e19 religious (eg, prohibition on extramarital and premarital sex), 8,17,20 sexual education (sex education and virginity pledges or less education about birth control and STIs), 13,16,17,21,22 or socioeconomic (eg, low or no education, parents highly educated, unemployment, low income, high income of parents, avoiding unwanted pregnancies). 7,8,12,23 It is now recognized that protected sexual activity in men is important for mental, sexual, and physical health at any stage of life. 24 Various population-and community-based studies have been published on the proportions of and factors affecting sexual abstinence in men younger than 60 years, mostly in reference to STIs and unwanted pregnancies, but no systematically reviewed literature was found with respect to men younger than 60 years.…”
Section: Introductionmentioning
confidence: 99%